Peningkatan Literasi Kesehatan dan Imunitas dalam Pencegahan DBD Melalui Edukasi dan Pelatihan Herbal - Efta Dhartikasari Priyana; Dwi Novri Supriatiningrum; Siti Fatimah; Yuyun Minarti (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Dengue Hemorrhagic Fever (DHF) remains a public health problem that requires preventive efforts through education and immunity improvement. This community service activity aims to increase public understanding of DHF and skills in producing herbal products as preventive measures. The methods used include counseling, demonstrations, and hands-on practice. The activity was conducted on January 18, 2026, at At-Taqwa Mosque, Banjarsari, Gresik, targeting Aisyah women’s groups. The results showed an increase in participants' knowledge about DHF and their ability to prepare immunomodulatory herbal drinks and understand herbal capsule concepts. Participants showed high enthusiasm through active involvement in discussions and practices. This activity contributes to improving community awareness of family-based DHF prevention and the use of local herbal resources.